Bioethics and artificial intelligence: between deliberation on values and rational choice theory - Pinto-Bustamante, Boris Julián; Riaño-Moreno, Julián C.; Clavijo-Montoya, Hernando Augusto; Cárdenas-Galindo, María Alejandra; Campos-Figueredo, Wilson David (Frontiers in Robotics and AI, 2023)
The present work revisits how artificial intelligence, as technology and ideology, is based on the rational choice theory and the techno-liberal discourse, supported by large corporations and investment funds. Those that promote using different algorithmic processes (such as filter bubbles or echo chambers) create homogeneous and polarized spaces that reinforces people’s ethical, ideological, and political narratives. These mechanisms validate bubbles of choices as statements of fact and contravene the prerequisites for exercising deliberation in pluralistic societies, such as the distinction between data and values, the affirmation of reasonable dissent, and the relevance of diversity as a condition indispensable for democratic deliberation.